Human computer interaction research in Web design and evaluation - Zaphiris, Panayiotis; Kurniawan, Sri, 1970-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2007)
"This is a comprehensive book on Human Computer Interaction and Web design focusing on various areas of research including theories, analysis, design and evaluation. It is not a book on web programming; it provides methods derived from research to help develop more user-friendly websites. It highlights the social and cultural issues in web design for a wider audience"--Provided by publisher.
The Usability Engineering Behind User-Centered Processes for Web Site Development Lifecycles / Theresa A. O'Connell, Elizabeth D. Murphy -- How Users View Web Pages: An Exploration of Cognitive and Perceptual Mechanisms / Rebecca A. Grier, Philip Kortum, James T. Miller -- A Qualitative Study in User's Information-Seeking Behaviors on Web Sites: A User-Centered Approach to Web Site Development / Napawan Sawasdichai -- Understanding the Nature of Task Analysis in Web Design / Rod Farmer, Paul Gruba -- From Behavior to Design: Answering the Questions of Who and What to Build Human-Centered Products and Information Systems / Catherine Forsman -- Design Methods for Experience Design / Marie Jefsioutine, John Knight -- Innovations in Collaborative Web Design: Methods to Facilitate Team Learning During Design / Madelon Evers -- Information Architecture and Navigation Design for Web Sites / David Benyon -- A Methodology for Web Accessibility Development and Maintenance / Julio Abascal, Myriam Arrue, Markel Vigo -- Usability Evaluation / Zhijun Zhang -- Walkthroughs in Web Usability: Cognitive, Activity, and Heuristic Walkthrough / Hokyoung Ryu -- User-Centered Evaluation of Personalized Web Sites: What's Unique? / Sherman R. Alpert, John G. Vergo -- Remote Usability Evaluation of Web Interfaces / Naouel Moha, Ashraf Gaffar, Gabriel Michel -- Modelling Interactive Behavior with a Rational Cognitive Architecture / David Peebles, Anna L. Cox.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 16, 2010).
Keywords: Web sites -- Design; Human-computer interaction; Electronic books